A fuzzy‐stochastic model for transversely fiber reinforced plastics. Issue 1 (17th December 2018) - Caylak, Ismail; Penner, Eduard; Dridger, Alex; Mahnken, Rolf
Abstract: This work is directed to aleatoric and epistemic uncertainties in the framework of constitutive modeling, which are taken into account by stochastic and fuzzy analysis. The stochastic part of material parameters are expanded with the multivariate polynomial chaos expansion, where for epistemic uncertainty the polynomial chaos coefficients are defined as design variables, which are modeled as fuzzy sets. The resulting min‐max optimization problem for the fuzzy analysis is approximated by α‐level discretization. A numerical example for the hybrid fuzzy‐stochastic analysis of material parameters is concerned with two different uncertain approximations to demonstrate the versatility of the proposed formulation.